A novel Agent Based Load Balancing Model for maximizing resource utilization in Grid Computing (Informatica, 2019)
Grid is the collection of geographically distributed computing resources. For efficient management of these resources, the manager must maximize its utilization, which can be achieved by efficient load balancing algorithm, The objective  of load balancing algorithms is to assign the load on resources to optimize resource use while reducing total jobs  execution time. the proposed agent based load balancing model aims to take benefit of the agent’s characteristics to generate an autonomous system. It also addresses similar systems drawbacks  such as instability, scalability or adaptability. The performances of the proposed algorithms were tested in Alea 2 simulator by using different parameters like response time, resources utilization and waiting time in the global queue. The performance evaluation appears that the proposed algorithm can enhance the overall performance of grid computing.